Underlying causes of Sexual Harassment in Institutions of Higher Learning in Uganda: Responses from Kyambogo University - Kebirungi, H. (South African Journal of Higher Education, 2021)
ABSTRACT This study used the social exchange theory and sexuality to investigate the underlying causes of sexual harassment in Institutions of Higher Learning in Uganda, with responses from Kyambogo University (KyU). Data were collected from internal and external stakeholder consultative meetings and workshops and the literature review. External participants were purposively selected from representatives of the Ministry of Education and Sports, public universities and non-governmental organizations, while internal participants were drawn from student leaders and university managers. Three meetings and two workshops were conducted with 390 participants (214 females and 179 males). The study provides evidence of sexual harassment (SH) at KyU. The underlying causes were limited awareness of SH among university stakeholders, students' background, poverty and a culture of silence. There is need to embark on a programme of building a safe and positive learning environment, supported by continuous sensitization and informed by an in-depth multi-stakeholder study on the status of SH at the University